The Post-verbal Effect of Negators in Mongolian Contradictory Negations Provides Support for the Fusion Model - Xu, Qinghong; Zhang, Shujun; Li, Jie; Wu, Baizhou; Qiu, Helin; Qilimuge, (Frontiers in Psychology, 2021)
There are two contending models regarding the processing of negations: the fusion model and the schema-plus-tag model. Most of the previous studies were centered on negations in languages, such as English and Mandarin, whose negators are positioned before the predicates. Mongolian, quite uniquely, is a language whose negation tags are located at the end of negative sentences, making them natural replicas of the schema-plus-tag model. Current study aimed to investigate the representation process of Mongolian contradictory negative sentences to shed lights on the contention between the two models. In the current study, a series of experiments, using sentence-picture verification paradigm, supported the fusion model by finding that: (i) Mongolian contradictory negative sentences were processed by representing the actual state of affairs, rather the negated state of affairs, at the initial stage (250 ms delay), and (ii) despite the fact that a post-position effect of negation tags was observed at the early stage by comparing the processing of Mongolian and Mandarin negative sentences, Mongolian-Mandarin bilinguals adopted the same representation strategy as Mandarin monolinguals.